PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAPKEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Destiana Permani Suci; Rustam Effendi (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
The purpose of this study was to determine the effect of leverage and profitability both simultaneously and partially on dividend policy on manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 - 2018.The data in this study were collected by documentation technique. The documentation technique is used to obtain data related to this research. The analysis technique used in this study is quantitative analysis using multiple linear regression. To test the data, the classical assumption test consists of multicollinearity test, heteroscedasticity test and autocorrelation test, whereas to test the hypothesis, the F test (simultaneous) and t test (partial test), and correlation coefficient (r) analysis, and coefficient of determination (r2).The results of this study indicate the value of fcount has a value lower than ftabel (4.644> 3.25) or significant F 0.016 <α 0.05, it can be concluded that Ha1 can be accepted simultaneously related to profitability and profitability towards dividends on manufacturing companies paid on the Exchange Indonesian effect. While partial shows that the leverage variable has a t-value of -1.335, which means tcount<ttable (-1.335 <2.026) and a significant leverage of 0.184> α 0.05 means that H02 is accepted and Ha2 is rejected, this leverage has no effect Partial dividend policy for manufacturing companies listed on the Indonesia Stock Exchange. The profitability variable has a tcount of 3.022 which means tcount>ttable (3.022> 2.026) and a significant profitability of 0.005 <α 0.05 means that Ha3 is accepted and H03 is rejected, this is related to the increase in profitability of the Indonesia Stock Exchange Keywords:Leverage, Profitability, Dividend Policy